Dirt persuasion : civic environmental populism and the heartland's pipeline fight - Moscato, Derek (Book collections on Project MUSE., 2022)
"Dirt Persuasion examines a watershed moment in U.S. environmental politics: the fight over the Keystone XL Pipeline. The complex interplay of resources extraction industries with grassroots environmentalism and advocacy has transformed the role of activists in the contemporary public sphere. Bold Nebraska's years-long fight against pipeline company TransCanada provides a compelling case study: a contemporary state-level organization that simultaneously challenged political and business leaders in its home state of Nebraska, at the national level in the United States, and in the foreign jurisdiction of Canada. Dirt Persuasion sheds light not only on the activism practices of social movements but also on the changing environments in which such actions are deployed. The KXL Pipeline fight represents a watershed moment not only for U.S. energy politics but also in the communication of environmental activism. The rural dimension of this environmental saga is critical: environmentalism must be understood from the perspective of the rural Americans who coexist with one of the planet's most delicate ecologies. Populism, rhetorical appeals, strategic advocacy framing, and media framing all factor prominently within the pipeline debate-leading to a civic environmental persuasion built on the attributes of narrative, engagement, hyperlocalization, and bipartisanship in order to build broad stakeholder support and influence public policy. "--